Cardiovascular manifestations identified by multi-modality imaging in patients with long COVID - Murata, Nobuhiro; Yamada, Akimasa; Fujito, Hidesato; Hashimoto, Naoki; Nagao, Tetsuro; Tanaka, Yudai; Fukumoto, Katsunori; Arai, Riku; Wakamatsu, Yuji; Ebuchi, Yasunari; Monden, Masaki; Kojima, Keisuke; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The possibility of permanent cardiovascular damage as a cause of cardiovascular long COVID has been suggested; however, data are insufficient. To investigate the prevalence of true cardiovascular disorders, particularly in patients with cardiovascular long COVID using multi-modality imaging. Methods: A total of 584 patients admitted to the hospital due to COVID-19 between January 2020 and September 2021 were initially considered. On outpatient follow-up, 52 (9%) were suspected to have cardiovascular long COVID, had complaints of chest pain, dyspnea, or palpitations, and were finally enrolled in this study. This study is registered with the Japanese University Hospital Medical Information Network (UMIN 000047978). Results: Of the 52 patients with long COVID who were followed up with outpatient clinic for cardiovascular symptoms, cardiovascular disorders were present in 27% (14/52). Among them, 15% (8/52) had myocardial injury, 8% (4/52) had pulmonary embolism, and 4% (2/52) had both. The incidence of severe conditions (36% [5/14] vs. 8% [3/38], p=0.014), ventilator requirement (21% [3/14] vs. 0% [0/38], p=0.003), and in-hospital cardiac events (71% [10/14] vs. 24% [9/38], p=0.002), were significantly higher in patients with cardiovascular disorders than in those without. Myocardial injury was associated with use of anti-rheumatic drugs (OR, 6.576; 95% CI 1.442-29.987; p=0.015), oxygen therapy (OR, 9.000; 95% CI 1.046-77.473; p=0.045), severe conditions (OR, 13.000; 95% CI 2.357-71.697; p=0.003), and in-hospital cardiac events (OR, 28.800; 95% CI, 3.241–255.948; p=0.003). Pulmonary embolism was significantly associated with chest pain as a symptom of long COVID (OR 6.364: 95% CI 1.023–39.575; p=0.047). Conclusions: The prevalence of true cardiovascular disorder in patients with cardiovascular long COVID in this study was approximately 30%. Myocardial injury was associated with disease severity, and pulmonary embolism was associated with chest pain after discharge. The prognosis of patients with and without true cardiovascular disorders was good. Early identification of long COVID with true cardiovascular disorder may contribute to symptom relief and improved prognosis in patients with long COVID.